Smart Control of Battery Energy Storage System in Harbour Area Smart Grid : A Case Study of Vaasa Harbour - Kumar, Jagdesh; Khan, Hussain Sarwar; Kauhaniemi, Kimmo (IEEE, 2021)
Battery energy storage system plays an essential role for optimally controlling and managing power of modern harbour grids so as to support electric vessels requiring onshore power supply and battery charging system. Designing an appropriate size of battery energy storage system of any harbour grid require precise data of power consumption as well future planned load. This paper presents a practical approach where a charge/discharge strategy is applied in such a way that peak-load demand of harbour grid is shaved off by discharging the battery during peak demand load and charging it during off-peak load demand. A suitable battery energy storage system along with its control algorithm is designed for Vaasa harbour grid with the obtained real data of annual power consumption and available power resources. Vaasa harbour grid model is developed in MATLAB/Simulink and a control algorithm is developed for the power flow to and from battery energy storage system by charging and discharging through bi-directional dc-dc converter. The results show that battery energy storage system is a suitable solution for harbour grids to cope with growing demand of new electric ships optimally in harbour grid without extensive renovation of the power supply infrastructure.
Keywords: Battery energy storage system; Harbour grid; Microgrid; Onshore power supply; Power control; fi=Sähkötekniikka|en=Electrical Engineering|